Some nineteenth century British scientists - Harre, Rom (Science and society (Oxford, England), 1969)
Some Nineteenth Century British Scientists presents the biographies of eight British scientists who represent the state of science in the second half of the Victorian era: Charles Wyville Thomson, James Murray, Arthur Cayley, Francis Galton, William Thomson, Lord Kelvin, Norman Lockyer, Sidney Gilchrist Thomas, and William Ramsay.